A voz e a palavra do movimento negro na Assembleia Nacional Constituinte (1987/1988): um estudo das demandas por direitos - Santos, Natália Neris da Silva (2015)
The objective of this study was to understand how the thematization of racism and racial issues were represented at the time the possibilities for dialogue between civil society and formal institutions of the Brazilian State are open: the National Constituent Assembly (NCA) 1987-1988. Through the study of documents that record the Black Movement’s participation along with the Constituent process, we sought to answer the following questions: 1. What were the demands claimed by the Black Movement organizations in the National Constituent Assembly? 2- What sort of arguments are mobilized by such actors / actresses to support the necessity and feasibility of the pleas insertion into the Constitution text? 3- These demands were included in the Constitution? In what way? In addition to the documentary research, there was literature on the sociopolitical context in question and on the anti-racist mobilization between the 1970s and 1980s. Through the study of social movement performance in the NCA and the balance of inclusions and exclusions of provisions in the Constitution, we pointed out the challenges faced by the Brazilian State in approaching this theme, the progresses and the persistence of certain past issues after almost three decades of the historical event studied herein.